Capital budgeting and entrepreneurial organizations: A survey of hospital practices - Shih-jen Kathy Ho; Lilian Chan; Daniel L. Tompkins (The Journal of Entrepreneurial Finance and Business Ventures, 2003)
Efficiency and effectiveness for all entrepreneurial firms requires that limited resources be put to their best use. Thus the acquisition of long-term assets is an important decision for any entrepreneurial firm. For hospitals, which have become entrepreneurial to survive in today's health care environment, long-term asset investment decisions have become critical to their survival. The objective of this study is to increase health care organizations' awareness of the important considerations in selecting and monitoring long-term investments. Our findings from a small sample of American hospitals indicate that payback method is the primary criterion for evaluating hospital's long-term investment projects. Also of note is the high proportion of hospitals whose approaches seem to incorrectly deal with the effects of inflation. On the other hand, the sample hospitals seem to be aware of the need to consider both tangible and intangible costs and benefits. They also exhibit awareness of the importance of follow up in the form of post audits.
Keywords: 650